DEEP INSIDE OF A PARALLEL UNIVERSE: RELIGIOUS ELEMENTS SURROUNDING THE STUDENT MOVEMENT IN SERBIA (Religious dialogue and cooperation, 2025)
Following the collapse of the concrete canopy at the newly reconstructed train station inNovi Sad, which killed sixteen people, Serbia has been witnessing the largest student movement inEurope since 1968. Students of diverse ideological, political, and religious backgrounds have cometogether to demand justice and accountability from a corrupt political establishment. This paperwill strive to explore the religious and quasi-religious elements of the movement – rituals of silence,pilgrimage, ascetic endurance, and communal feasting – interpreted through a functional and anthropologicalapproach to religion inspired by Durkheim. The study combines qualitative mediadiscourse analysis of secular and religious communications (November 2024 to June 2025) withthe author’s direct anthropological observation of protest events. This dual perspective enables anexamination of how collective rituals and moral symbols emerged both in representation and inpractice. The protests drew strong reactions from Serbian Orthodox Church dignitaries and otherpublic voices, which will be examined through critical discourse analysis, focusing on how churchstaterelations and religious or ideological divisions were framed. The question of various collectivesubjects fulfilling the usual societal functions of religion will be posed.
Keywords: anthropology of religion; media discourse analysis; student movement; Serbia; Durkheim; civic ritual; religion; politics